Nature-themed apps, 2013 : data scrape of Google Play - Jepson, P; Abele, S; Ladle, R (University of Oxford, 2015)
Data generated from a randomized English-language data scrape of Google Play Store between February and April 2013 using nature-related search words. This returned .36,304 apps that were manually reviewed by two people working together to remove nonn-nature-related apps - semantic complexity precluded fully-automated pruning. Through this process, 6301 apps were identified as nature themed. These were then assigned to one or more of six major use categories following an interactive process of automated keyword classification and manual review